Retailing management - Levy, Michael; Weitz, Barton A. (McGraw-Hill Irwin, 2007)
Offers coverage of the topics and developments in retailing including globalization, customer relationship management programs, multi-channel retailing, supply chain management, and the use of the Internet to improve operating efficiencies and customer service. This book includes examples of retailers, their practices and retail facts.